2003
DOI: 10.1097/01.rli.0000065696.41011.ce
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Acute Cyclosporine Nephrotoxicity and Acute Tubular Necrosis Using Enalaprilat Renal Scintigraphy in Rats

Abstract: These results suggest that enalaprilat renal scintigraphy could be used clinically in differentiating acute CsA nephrotoxicity from ATN after renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Some males and females in the high dose group showed variable leukocytosis or leukocytopenia (6.12-25.86 £ 10 9 /L in the male control group versus 1.44-73.71 £ 10 9 /L in the male high dose group; 4.02-12.91 £ 10 9 /L in the female control group versus 1.00-83.96 £ 10 9 /L in the female high dose group), but no signiWcant or consistent pattern of change was observed. Serum concentrations of blood urea nitrogen and creatinine are used nearly exclusively to provide clinical information regarding overall renal function (Kim et al, 2003b). In general, it is known that creatinine levels provide the most accurate information about the renal function.…”
Section: Parametermentioning
confidence: 99%
“…Some males and females in the high dose group showed variable leukocytosis or leukocytopenia (6.12-25.86 £ 10 9 /L in the male control group versus 1.44-73.71 £ 10 9 /L in the male high dose group; 4.02-12.91 £ 10 9 /L in the female control group versus 1.00-83.96 £ 10 9 /L in the female high dose group), but no signiWcant or consistent pattern of change was observed. Serum concentrations of blood urea nitrogen and creatinine are used nearly exclusively to provide clinical information regarding overall renal function (Kim et al, 2003b). In general, it is known that creatinine levels provide the most accurate information about the renal function.…”
Section: Parametermentioning
confidence: 99%
“…But the organs coefficient values of liver and kidney were increased in Group IV. The levels of ALT and AST activity can reflect the damages of liver, and then serum concentrations of BUN and CRE were used nearly exclusively to provide clinical information regarding overall renal function (Kim et al, 2003). The results showed that all the serum biochemistry parameters of experiment groups had no statistically significant difference compared with those of the control group (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%